2016
DOI: 10.1177/0284185116641345
|View full text |Cite
|
Sign up to set email alerts
|

Duplex ultrasound for identifying renal artery stenosis: direct criteria re-evaluated

Abstract: Background Renal artery duplex ultrasound (RADUS) is an established method for diagnosis of renal artery stenosis (RAS), but there is no consensus regarding optimal RADUS criteria. Purpose To define optimal cutoff values for RADUS parameters when screening for RAS using intra-arterial trans-stenotic pressure gradient measurement (PGM) as reference. Material and Methods The renal arteries of 58 consecutive patients evaluated for renovascular hypertension were examined by RADUS and PGM. Conclusive measurements w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
(39 reference statements)
0
11
0
6
Order By: Relevance
“…During RDU examination, synthetic judgment of multiple parameters, including PSV, RAR, renal interlobar velocity ratio (RIR), AT, and RI, are essential to correct diagnosis. For example, Zachrissonet al [27] reported that RAR is a more sensitive criterion than traditional RDU criteria when screening patients with clinical suspicion of RAS. Additionally, factors other than RAS, such as left heart insufficiency, mitral valve disease, and aortic disease, could affect the results of PSV and RAR.…”
Section: Discussionmentioning
confidence: 99%
“…During RDU examination, synthetic judgment of multiple parameters, including PSV, RAR, renal interlobar velocity ratio (RIR), AT, and RI, are essential to correct diagnosis. For example, Zachrissonet al [27] reported that RAR is a more sensitive criterion than traditional RDU criteria when screening patients with clinical suspicion of RAS. Additionally, factors other than RAS, such as left heart insufficiency, mitral valve disease, and aortic disease, could affect the results of PSV and RAR.…”
Section: Discussionmentioning
confidence: 99%
“…• Рекомендуется собирать полный медицинский и семейный анамнез для оценки семейной предрасположенности к АГ и ССЗ [51,52] [64].…”
Section: жалобы и анамнезunclassified
“…• Всем пациентам с нарушением функции почек, альбуминурией и при подозрении на вторичную АГ рекомендуется проведение УЗИ почек и дуплексного сканирования артерий почек с целью оценки размеров, структуры, а также наличия врожденных аномалий почек или стеноза почечных артерий [60,61,64].…”
Section: еок/еоаг Iibв (уур B удд 2)unclassified
“…Причиной стеноза почечных артерий (ПА) почти в 85 % случаев являются атеросклероз или некоторые формы фибромускулярной дисплазии (примерно 15 %). Популяционные исследования показывают, что 6,8 % лиц старше 65 лет имеют стеноз ПА с уменьшением более 60 % просвета сосуда [18]. Предполагается, что 1-5 % больных с АГ могут иметь компонент РВГ.…”
Section: клинические семинары §unclassified
“…Ультразвуковая допплерография ПА с измерением пиковой систолической скорости кровотока обладает чувствительностью более 85 % и специфичностью 92 % для атеросклеротического поражения с сужением просвета более 60 % [18]. Для данного метода характерны ложноотрицательные результаты, зависящие от специалиста, проводящего исследование, и технических причин.…”
Section: кому необходимо проводить скрининг?unclassified